“Nós realizamos a utopia”: transformação da vida cotidiana das mulheres trabalhadoras na Revolução Espanhola - Martins, Karina Oliveira (2019)
This research analyzes the transformation of the daily life of working women in the Spanish Revolution (1936-1939), with emphasis on the activities of the Mujeres Libres organization, as well as the relationship between gender, daily life and social transformation. The daily life referenced in Agnes Heller's dialectical materialist historical perspective is the central category of this research, and from it the present analyzes are grounded and articulated. The basis of these analyzes was the bibliographical and documentary research. The work is divided into four chapters, the first one develops considerations on the social being, work and structures of daily life, the second is reflections on the relationship between gender, women's history and sex, sexual division of labor, patriarchy, relationship between gender, class and daily life, the third one is about Spanish history: its socio-political reality, the reality of women, its authentic anarchism and the beginning of the Spanish Revolution; in the life of women in the Spanish Revolution, dealing with issues such as work, prostitution, political engagement, militia, among others. In the development of this work the relationship between daily and non-daily life was grasped, in which the transformation of daily life is essential for a revolutionary process. This is especially true for women who, because of patriarchy, have been relegated to everyday spheres, especially the private sphere. In such a situation, working women suffer exploitation of labor and also gender oppression, there being an antagonism of class and gender, such aspects can only be overcome together, which was outlined embryonic in the Spanish Revolution. In it, women had new possibilities of developing their own lives and an increase in daily freedom. For this, his organization and confrontation with and against his own classmates was fundamental. However, this process of transformation was conflicting and contradictory, presenting limits.